Use of Herbs for Health in The Community of Mueang District Khon Kaen Thailand: Use of Herbs for Health in The Community of Mueang District Khon Kaen Thailand - Vivi Silawati; Retno Widowati; Triana Indrayani; Siti Lomrah; Aquarini Pajriyanti Puteri; Lusi Oktaviani; Siti Puteri Utami (International Journal of Community Services, 2025)
Many members of the community do not have sufficient knowledge about the benefits of herbs and how to use them properly. This often leads to distrust of the effectiveness of herbs as an alternative treatment. The habit of consuming modern medicines is more dominant than herbs. This is triggered by the perception that modern medicine provides results faster. Limited access to information about the types of herbs and their benefits, as well as limited access to quality herbal products in some areas. In 2024, there were 56 PCIM members studying in Thailand and around 130 Indonesian students studying internationally at Khoen Kaen University (KKU). Around 40% of these students experienced physical complaints such as colds, nausea, vomiting and dizziness due to physical conditions, weather and other things. The use of herbs/herbal medicine as an effort to maintain health and treat various diseases that have been passed down from generation to generation. This legacy is expected to continue to be utilized by the younger generation, especially international students, as an alternative to increase endurance and overcome physical complaints. Indonesia and Thailand have similarities in the use of herbs as medicine, including ginger, melon, nutmeg, cinnamon, chili, cloves, galangal, lemongrass, honey and others. The implementation of community service was carried out in Mueang District, Khon Kaen, Thailand, on August 28, 2024 with 20 participants. After being given counseling and practice in making herbal drinks, participants were able to learn the types, benefits and how to process spices as herbal drinks to be used as safe and effective alternative medicine.